Національні стратегії штучного інтелекту країн Європи - Дацюк, Г. К. (ХНУРЕ, 2023)
The rapid growth of artificial intelligence (AI) has brought numerous benefits to societies worldwide, but it also poses challenges. The European Union (EU) aims to become a global center for AI while ensuring that it remains human-oriented, trustworthy, and based on European values and fundamental rights. Several European countries have launched national strategies to invest in AI and address ethical concerns